The Historicity of Artifacts: Use and Counter-Use. (4th February 2022) - Evnine, Simon J.
Inspired by Sara Ahmed's notion of 'queer use, ' I present and extend a neo-Aristotelian theory of artifacts to capture what I call 'counter-use.' The theory of artifacts is based on the idea that what they are, how they come to be, and what their functions are cannot be understood independently from each other. They come to exist when a maker imposes the concept of their substantial kind onto some matter by working on the matter to make an artifact of that kind out of it. The extensions to this core theory that I describe are two. First, I show how using can be a kind of making and how disparate users may form what Benedict Anderson calls an imagined community. Second, I describe what I call an artifact's historicity and suggest that, like its substantial kind, an artifact's historicity is essential to it. On this basis, I characterize counter-use as use of an artifact by an imagined community that re-arranges an object's historicity and hence brings into existence a numerically distinct object. Thus, politically motivated counter-use has genuine ontological implications.